Determinação da resistência de Euschistus heros F. 1798 (Hemiptera: Pentatomidae) a diferentes inseticidas comerciais - Cruz, Victor Wilio Bombarda Souza (2017)
Neotropical brown stink bug (Euschistus heros) (Hemiptera: Pentatomidae) is a potentially harmful insect of soybean crop, causing directly or indirectly damage due to the injection of toxic substances into the plant. Its control is done mainly by the use of insecticides. Although this control is efficient, there are reporting cases of resistance of these insects to such products. Therefore, this study evaluated the E. heros resistance to different insecticides in different rates in laboratory and also a control efficiency of the bugs according to the location of the insects in the canopy layer from the plant at the field. For the realization of the bioassays, specimens adultos of E. heros were collected in soybean crops fields in Dois Vizinhos, Paraná, transferred to the Biological Control Laboratory I at the Federal Technological University of Paraná, Campus Dois Vizinhos and submitted to topical application of 5 µL of the insecticides doses. The commercials products used were Connect [marca registrada], Engeo [marca registrada] Pleno [marca registrada] and Orthene [marca registrada] using the recommended dose, two, three and four times the amount recommended by the label of the product. For each treatment (dose), twenty replicates were used, being each adult insect considered a replicate. For the performance at the field, were collected native specimens of E. heros from soybean crop fields in Dois Vizinhos, Paraná, and kept in plastic container, which had the lid and bottom base altered, fixed between the line plants. Was applied a mix of Connect plus Talstar, dissolved in 200 liters of water per hectare and applied in the area using a self-propelled sprayer. The experiment was constituted by 3 treatments with 4 replicates per treatment, in which each treatment was a canopy layer from the plant (upper third, middle third and lower third. All the insects that were submitted to the laboratory experiment, died, independent of the dosage used. The field experiment figures out that neotropical brown stink bugs in the upper third of the plant extract had 100% of mortality, while in the middle third and lower third, the results did not exceed 75% of the control.